Sexual violence victimization and suicide: Testing a coping‐mental health framework. Issue 3 (15th February 2021) - Kaniuka, Andrea R.; Desmarais, Sarah L.; Cramer, Robert J.; Stoner, Julie E.; Veri, Shelby; Wright, Susan; Gemberling, Tess M.; Nobles, Matt R.; Holley, Sarah R.
Abstract: Sexual violence victimization is a prevalent public health concern. However, little research has investigated the factors linking sexual violence victimization to suicidal thoughts and behaviors (STBs). The current study tested the applicability of the psychological mediation framework, a coping‐mental health model, for the prevention of STBs among victims of sexual youviolence. Furthermore, the current study explored whether sexual orientation moderated the progression from sexual violence victimization to STBs. Data were drawn from an online survey of victimization experiences and health ( N = 2175). Bootstrap mediation tested whether the association of sexual violence victimization and STBs was mediated by emotion regulation strategies (cognitive reappraisal and expressive suppression) and psychopathology (anxiety, depression, and posttraumatic stress disorder). Multiple‐groups analysis tested whether links within the mediation effects varied by sexual orientation. Bivariate findings showed that: (1) sexual minority persons were more likely to report sexual violence victimization and (2) cognitive reappraisal was more meaningfully associated with mental health among sexual minority persons. Sexual violence victimization was associated with STBs via a serial mediation through emotion regulation and psychopathology. The association between psychopathology and STBs was stronger among sexual minority compared with heterosexual respondents. Physical violence victimization was associated with STBs for heterosexual but not sexual minority persons in a follow‐up model. Findings support an emotion regulation‐mental health framework for the prevention of suicide among victims of sexual violence. Research and training implications are discussed.